Prevalence and associate risk factors of asymptomatic bacteriuria in pregnancy with bacterial pathogens and their antimicrobial susceptibility in a tertiary care hospital - Rohini, Udayagiri Venkata; Reddy, Gurram Swetha; Kandati, Jithendra; Ponugoti, Munilakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Asymptomatic bacteriuria (ASB) is defined as the presence of actively multiplying bacteria, which is greater than 105/ ml of urine within the urinary tract excluding the distal urethra, at a time when the patient has no symptoms of UTI. Untreated and undiagnosed ASB is associated with adverse maternal and perinatal outcomes. The objective was to determine the profile, prevalence, microbiological isolates with susceptibility, and risk factors of ASB among pregnant women attending an antenatal clinic at a tertiary care hospital, Andhra Pradesh, India. Methods: A prospective cross sectional study with 200 pregnant women was conducted for a period of 3 months from January to March 2016. The mid- stream urine specimen was collected and processed from all the cases and social and baseline obstetric data was collected. The isolates from all the cases of ASB were identified by standard biochemical tests. Antimicrobial susceptibility was performed by Kirby- Bauer disc diffusion method and interpreted as per CLSI guidelines. Results: Prevalence of ASB in our study was 30.5%, mean age of the cases was 27.3± 2.9 years. ASB was most common in 25- 30 year’s age group, during 3rd trimester and among multiparous and multigravidae. Previous history of UTI, pre-eclampsia was having significant association among cases with ASB. Escherichia coli was the predominant isolate in the study followed by K. pneumoniae, CONS (Coagulase-Negative Staphylococci), Staphylococcus aureus, citrobacter and Enterococci. Conclusions: Undiagnosed and untreated asymptomatic bacteriuria is associated with complications during pregnancy. Hence routine screening of antenatal women during all trimesters must be considered in preventing the complications and adverse foetal outcomes particularly with known risk factors like increasing age, multiparity and previous history of UTI.